Antiviral drug discovery with an optimized biochemical dengue protease assay: Improved predictive power for antiviral efficacy - Lang, Johannes; Dutta, Sudip Kumar; Leuthold, Mila; Reichert, Lisa; Kühl, Nikos; Martina, Byron; Klein, Christian D. (Antiviral research, 2025)
The viral NS2B-NS3 protease is a promising drug target to combat dengue virus (DENV) and other emerging flaviviruses. The discovery of novel DENV protease inhibitors with antiviral efficacy is hampered by the low predictive power of biochemical assays. We herein present a comparative evaluation of biochemical DENV protease assay conditions and their benchmarking against antiviral efficacy and a protease-specific reporter gene assay. Variations were performed with respect to pH, type of detergent, buffer, and substrate. The revised assay conditions were applied in a medicinal chemistry effort aimed at phenylglycine protease inhibitors. This validation study demonstrated a considerably improved predictive power for antiviral efficacy in comparison to previous approaches. An extensive evaluation of phenylglycine-based DENV protease inhibitors with highly diverse N-terminal caps indicates further development potential in this structural region. Furthermore, the phenylglycine moiety may be less essential than previously assumed, providing a development option towards reduced lipophilicity and thereby an improved pharmacokinetic and toxicity profile.